Diseño de una estrategia de selección del fluido ácido usado en procesos de estimulación en yacimientos de carbonatos (2019)
In Colombia, this formation is considered as a formation of carbonates, since it is formed by intercalations of black shales (some calcareous), micritical and sparritic limestones, some of them with calcareous concentrations of up to 2 m in diameter and black chert. For the present study, it is intended to collect mineralogical information from the Villeta Caliza A formation, to determine the best acid system that can be use in acid fracturing processes in this formation, by means of the development of a matrix that uses a multicriteria analysis to establish the best recommendation regarding the concentration and composition that the acid system must have.